Annona muricata L)(The Effect of Sulfite Soaking and Benzoic Addition to Soursop Puree) - Sunarto, Paulus; Djubaedah, Endah (Warta Industri Hasil Pertanian, 1988)
A study on soursop puree has been conducted to decide the best processing stages. The effect of sulfite soaking and benzoic addition to the products has also been studied. Observation was done on moisture content, sugar content and ascorbic acid content and organoleptic test during storage. The moisture content, sugar content and ascorbic acid content of soursop puree were decreased during storage. The result showed that up to 4 weeks of storage, all of the treatments were acceptable.